2005
DOI: 10.1182/blood-2005-02-0674
|View full text |Cite
|
Sign up to set email alerts
|

KLF2 is essential for primitive erythropoiesis and regulates the human and murine embryonic β-like globin genes in vivo

Abstract: The Krü ppel-like factors (KLFs) are a family of C2/H2 zinc finger DNA-binding proteins that are important in controlling developmental programs. Erythroid Krü ppel-like factor (EKLF or KLF1) positively regulates the ␤-globin gene in definitive erythroid cells. KLF2 (LKLF) is closely related to EKLF and is expressed in erythroid cells. KLF2 ؊/؊ mice die between embryonic day 12.5 (E12.5) and E14.5, because of severe intraembryonic hemorrhaging. They also display growth retardation and anemia. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 25 publications
1
80
0
Order By: Relevance
“…KLF2 is necessary for primitive erythropoiesis, and positively regulates embryonic globin gene expression, as shown in KLF2 knockout and erythroid-conditional knockout mouse embryos. 11,19,20 Global gene expression assays indicate that many genes that are important in the processes of development, differentiation and cell migration are dysregulated in KLF2-/-compared to wild-type primitive erythroid cells. 21 Ablation of KLF2 causes lethality between E11.5 and E14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KLF2 is necessary for primitive erythropoiesis, and positively regulates embryonic globin gene expression, as shown in KLF2 knockout and erythroid-conditional knockout mouse embryos. 11,19,20 Global gene expression assays indicate that many genes that are important in the processes of development, differentiation and cell migration are dysregulated in KLF2-/-compared to wild-type primitive erythroid cells. 21 Ablation of KLF2 causes lethality between E11.5 and E14.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA synthesis and quantitative reverse-transcriptase PCR (qRT-PCR) were performed as previously described. 11,12,19,20 Primer sequences for qRT-PCR are listed in Online Supplementary Table S1.…”
mentioning
confidence: 99%
“…Forced overexpression of KLF2 induced a quiescent T cell phenotype whereas KLF2-null T cells exhibited a spontaneously activated phenotype (9). More recently, KLF2 has also been implicated in the regulation of embryonic globin gene synthesis (10).…”
mentioning
confidence: 99%
“…We have determined the chromosomal location of the chicken KLFs, and they are presented in Table 1. Although the EKLF and KLF2 genes are located in close proximity on the same chromosome in mouse and human (Basu et al, 2005), this finding is not the case in chicken. Chicken EKLF has three exons, as do its mammalian homologues.…”
Section: Identification Of Chicken Eklfmentioning
confidence: 74%
“…Recently, we reported that KLF2/LKLF is essential for primitive erythropoiesis and regulates the embryonic globin genes in vivo (Basu et al, 2005). These mice also have a defect in blood vessel formation and die between E12 and E14 (Kuo et al, 1997;Wani et al, 1998).…”
Section: Introductionmentioning
confidence: 96%